Enhanced oxygen reduction reaction activity of nitrogen-doped graphene/multi-walled carbon nanotube catalysts in alkaline media. (21st December 2016) - Ratso, Sander; Kruusenberg, Ivar; Joost, Urmas; Saar, Rando; Tammeveski, Kaido
Abstract: In this work, the electroreduction of oxygen on nitrogen-doped graphene and multi-walled carbon nanotube (MWCNT) composite catalysts is investigated. Acid-treated MWCNTs and graphite oxide were doped using biuret, carbohydrazide and semicarbazide hydrochloride as the nitrogen precursors. The reactants were mixed with carbon nanomaterials and pyrolysed in an inert atmosphere at 800 °C. Scanning electron microscopy was used to characterise the surface morphology of catalysts and X-ray photoelectron spectroscopy (XPS) was used to determine the surface content of the catalysts. XPS revealed different contents of nitrogen gained by using different nitrogen precursors, which were tied to electrochemical activities observed in this work by using the rotating disk electrode (RDE) method. The catalysts revealed high oxygen reduction reaction (ORR) activity even at low loadings and excellent stability over 1000 potential cycles. This indicates their applicability as cathode materials in alkaline anion exchange membrane fuel cells. Highlights: Highly active N-doped graphene/carbon nanotube composite catalysts are synthesised. Electrocatalytic ORR activity for different nitrogen-doped composites is compared. The reasons for the difference in the ORR activity are discussed. The stability of the N-doped nanocarbons during 1000 potential cycles is assessed.